AB0200 High expression of toll like receptors 7 and interleukin 18 in lupus nephritis. (23rd January 2014) - Spinelli, F.R.; Truglia, S.; Alessandri, C.; Bombardieri, M.; Ceccarelli, F.; Martinelli, F.; Miranda, F.; Conti, V.; Perricone, C.; Giannakakis, C.; Faraggiana, T.; Valesini, G.; et al.
Abstract : Background: Both humoral and cellular immune mechanisms are involved in the development of lupus nephritis (LN). Due to the ability to recognize microbe specific and endogenous nucleic acids, Toll-like receptors (TLRs) may contribute to renal inflammation. Objectives: Aim of this study was to evaluate the expression of TLR3, TLR7, TLR8 and IL18 in the kidney of SLE patients. Methods: Kidney sections have been analyzed by standard immunohistochemistry using anti-human TLR3, 7, 8 and IL-18 MoAb. Using dedicated software, all the sections were analyzed for number of nuclei per mm 2 positive for TLR3/7/8 and IL18. Results: Table 1 shows glomerular and tubular expression of TLRs and IL18 in 20 kideny sectiona from LN patients. No difference in glomerular and tubular expression of TLRs and IL18 among histological classes was observed; only glomerular TLR3 was higher in class III than in IV (p=0.004). In the whole population and in classes III and IV, glomerular and tubular expression of TLRs did not differ one from the other; as for IL18, glomerular expression was higher than the tubular one (p=0.03) in class IV. Considering all the biopsies, both tubular and glomerular TLR7 expression was significantly higher than TLR3 and TLR8 expression (p<0.005). In class III, glomerular and tubular TLR3 was higher than TLR8 (p=0.0005 and p=0.004); glomerular and tubular TLR7 was higher than TLR8 (p=0.009 and p=0.006). In class IV glomerular and tubular TLR7 was higher than TLR3 (p=0.02 and p=0.03) and TLR8 (p=0.0009 and p=0.002). Conclusions: We observed a high number of nuclei expressing IL18 and TLR7, a moderate number expressing TLR3 and a low number expressing TLR8 in tubules and glomeruli of LN patients. This data reinforces the hypothesis that activation by endogenous TLRs ligands may contribute to the persistent expression of proinflammatory cytokines in SLE patients. Disclosure of Interest: None Declared